A rare presentation of primary apla and pulmonary thrombolism - Chinnasamy, Vignesh; Kumar, K. Mahendra; T., Gnanadeepan (International Journal of Advances in Medicine, 2023)
Antiphospholipid syndrome (APS) is a state of hypercoagulation, causing thrombus in artery, vein and capillaries, with or without obstetrical events with the presence of autoantibodies, which includes lupus anticoagulant, anticardiolipin antibodies and anti-β2-glycoprotein 1 antibodies. It has variable clinical presentations such as vascular thrombosis and obstetrical complications, pulmonary thromboembolism (PTE), pulmonary hypertension, and acute respiratory distress syndrome. Hereby we presented a case of young male who came to our hospital with hemoptysis and isolated pulmonary embolism, with the background of APS which is rare. Hemoptysis and pulmonary thromboembolism both being fatal emergencies requiring completely different management methods.